Pengembangan Sistem Informasi Hamzar Eduline Untuk Meningkatkan Kinerja Guru Sekolah Dasar di Yayasan Maraqitta’limat - Muhammad Fadlurrahman; Ida Bagus Putu Arnyana; I Gede Margunayasa (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop the Hamzar Eduline Information System, a new application designed to improve the performance of elementary school teachers at the Maraqitta’limat Foundation. The system was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The analysis stage was conducted to identify the needs of teachers and principals regarding performance assessment tools. During the design and development stages, the system was built using Google Sites and equipped with objective-based performance test features, featuring an attractive design tailored to user needs. The product was validated by subject matter experts and information system experts, who awarded a validity score of 91.67 (categorized as very valid). A practicality test involving the school principal and teachers yielded excellent results, with the principal giving a score of 96.36 and teachers giving an average of 3.52 out of 4. The effectiveness test showed that 75 percent of the teachers reached the good to very good category in performance assessment after using the information system. These results demonstrate that Hamzar Eduline is a new, effective, practical, and feasible application to support the improvement of elementary school teacher performance.